Revolving loan funds and credit programmes for fishing communities : (Food and Agriculture Organization of the United Nations, 1989)
Revolving loan funds are part of many fisheries development projects: initial considerations, lending policy, institutional arrangements, lending procedures, repayment and loan recovery procedures and revolving fund administration.